Detection by electron microscope of rod-shaped organisms in synovial membrane from a patient with the arthritis of Whipple's disease. Issue 6 (December 1976) - Hawkins, C F; Farr, M; Morris, C J; Hoare, A M; Williamson, N
Abstract : Rod-shaped organisms identical to those present in the jejunal mucosa have been found in the synovial membrane of a patient with Whipple's disease. These probably caused inflammatory changes which sere reflected in an increase of the cellular content and high enzyme levels (acid phosphatase and 5-nucleotidase) of the synovial fluid. Tetracycline was effective in controlling the bowel lesion but only had a temporary effect upon the arthritis. Erythromycin controlled both the bowel lesion and the arthritis.